Use of Mobile Apps for epidemic surveillance and response - availability and gaps. - Biswajit Mohanty; Abrar Chughtai; Fethi Rabhi (University of New South Wales, 2019)
'Background': Early detection of disease outbreaks, using appropriate surveillance methods, is a basic principle for effective control of epidemics. Indicator-based surveillance methods, such as comprehensive surveillance, sentinel surveillance and syndromic surveillance, have been routinely utilized for early epidemic detection to minimize mortality and morbidity related to emerging infectious disease threats. In addition, event-based surveillance uses unstructured data sources to detect and monitor outbreaks such as media reports, social media and websites. The use of mobile phone technology is growing in many low and middle-income countries, which has made mHealth an efficient means of health communication in such countries for epidemic surveillance, mitigation and response.  Mobile Apps may draw data from validated health sources or unvalidated public sources and convey information to responders. The aim of this study was to review mobile Apps used for epidemic surveillance and response.    'Methods': A review of Google Play and the App Store was conducted from June 2018 to August 2018 for Apps containing the words "epidemic", "outbreak", "pandemic", "public health", "infectious diseases", "infection", "bioterrorism" or "CBRNE", "surveillance". Available Apps were analysed by the intended user, purpose, platform, functions and number of downloads. 'Results': We found a total of 106 Apps in an initial search, and of those 80 Apps did not meet the selection criteria and were excluded. Finally, 26 relevant surveillance Apps, including 21 free of charge and 5 paid Apps, were included in this review. Of these, 17 Apps are for single disease surveillance, 7 Apps for multiple disease surveillance and 2 Apps provides information on possible bioterrorism agents. The intended user varied from the general public (18 Apps) to health practitioners (4 Apps) and remaining 4 Apps intended for both general public and health practitioners. The Apps included real-time tracking in an interactive map (10 Apps), daily notification alerts (3 Apps), user function to report diseases/ outbreaks (4 Apps) and multiple disease tracking options (7 Apps). The most downloaded Apps were Sickweather with 100,000+ downloads and HealthMap with 10,000+ downloads. Only 4 Apps were available on both Android and iOS platforms. 'Conclusion': There are at least 26 mobile Apps for surveillance of epidemics, mostly free of charge and mostly for laypeople. Among them, HealthMap is the most comprehensive, but by far the greatest number of downloads was for a consumer App, Sickweather.  Some Apps can provide real-time tracking and interactive maps. However, limitations included unavailability of Apps suitable for general public or surveillance of potential bioterrorism incidents, limited geographic or disease relevance, and high cost for some Apps. There is great potential to utilize existing Apps and develop new ones, especially which meet the needs of health professionals and public health authorities for real-time disease surveillance.